Fighting the hunger games through permaculture: a scoping review to inform urban planning - Janse van Rensburg, Denise; Puren, Karen (Frontiers in Sustainable Cities, 2023)
In 2020, more than seven million people across the globe starved, and 868 million people were estimated to be undernourished globally. Although the eradication of hunger is a noble goal, the continuously growing world population together with the warning of a future characterized by food insecurity spells ongoing hardship for the future of humankind. This study explores the extent of permaculture literature to establish its potential place within urban systems. A scoping review looks at permaculture literature from the last 8 years to establish its benefits and limitations, possibly within urban systems. Permaculture is mainly studied from social, environmental, and economic perspectives, and mostly within rural contexts. Urban planning directly concerns the social, environmental, and economic dimensions of urban systems. This study thus reveals the possible merits of permaculture for food production within urban systems; however, certain limitations should be kept in mind that may encumber the implementation of permaculture by urban planning.